The Mechanism of Endothelium-Independent Relaxation Induced by the Wine Polyphenol Resveratrol in Human Internal Mammary Artery - Novakovic Aleksandra; Gojkovic-Bukarica Ljiljana; Peric Miodrag; Nezic Dusan; Djukanovic Bosko; Markovic-Lipkovski Jasmina; Heinle Helmut (Elsevier, 2006)
Abstract.: Resveratrol, a stilbene polyphenol found in grapes and red wine, produces vasorelaxation in both endothelium-dependent and endothelium-independent manners. The mechanisms by which resveratrol causes vasodilatation are uncertain. The aim of this study was to investigate the mechanism(s) of endothelium-independent resveratrol-induced vasorelaxation in human internal mammary artery (HIMA) obtained from male patients undergoing coronary artery bypass surgery and to clarify the contribution of different K+ channel subtypes in resveratrol action in this blood vessel. HIMA rings without endothelium were precontracted with phenylephrine. Resveratrol induced a concentration-dependent relaxation of the HIMA. A highly selective blocker of ATP-sensitive K+ channels, glibenclamide, as well as nonselective blockers of Ca2+-sensitive K+ channels, tetraethylammonium and charybdotoxin, did not block resveratrol-induced relaxation of HIMA rings. 4-Aminopyridine (4-AP), non selective blocker of voltage-gated K+ (KV) channels, and margatoxin that inhibits KV1.2, KV1.3, and KV1.6 channels abolished relaxation of HIMA rings induced by resveratrol. In conclusion, we have shown that resveratrol potently relaxed HIMA rings with denuded endothelium. It seems that 4-AP- and margatoxin-sensitive K+ channels located in smooth muscle of HIMA mediated this relaxation. Keywords:: resveratrol, vasorelaxation, human internal mammary artery, K+ channel